Comunicação interprofissional na atenção primária à saúde: scoping review - Cavalcante, Francisco Marcelo Leandro (2024)
Interprofessional Communication is an essential collaborative competence in Primary Health Care, which makes it possible to integrate multidisciplinary knowledge and practices, fosters shared decision-making, dialogue, and recognition of the role of each member in the team. When fragile, it compromises the problem-solving, quality and safety of health care. Thus, the objective was to map the scientific literature on Interprofessional Communication in Primary Health Care. This is a scoping review, carried out from November 2023 and March 2024, in accordance with Joanna Briggs Institute’ recommendations. The databases and portals used were Scopus, Web of Science, Medical Literature Analysis and Retrieval System on Line, Scientific Electronic Library Online, Latin American and Caribbean Literature in Health Sciences, Nursing Database, Spanish Bibliographic Index in Health Sciences, via the Virtual Health Library, Brazilian Digital Library of Theses and Dissertations, CAPES Catalog of Theses and Dissertations. For analyze the studies, the Context-Mechanism-Result configuration was used. It retrieved 12,392 publications, of which 58 were included in the final sample. Regarding to the contexts linked to Interprofessional Communication in Primary Care, it revealed favorable scenarios, in which communication was operationalized in a respectful, integrated, and democratic manner; but also, unfavorable contexts, marked by a lack of effective communication, hierarchical structures, lack of openness on the part of professionals to communication and collaborative moments. As a result, 64 mechanisms that hinder Interprofessional Communication were identified, the predominant ones being the occurrence of weak communication between professionals, a professional attitude that devalues communication and teamwork, work overload, weak communication channels, weak formal information sharing and professional hierarchies. Among the facilitating mechanisms, out of a total of 47 identified, effective, open, and respectful communication between professionals, formal meetings, the use of Information and Communication Technologies, formal and informal communication, collaborative work, electronic health records in medical records, respect, empathy, interprofessional relationships and case discussions prevailed. In view of these mechanisms, it was clear that when Interprofessional Communication is developed in a weak way, it results in a fragile dialogical process, conflicts, frustration and low interprofessional cooperation. However, when it is effective, it makes it possible to strengthen interprofessional collaboration, shared decision-making, effective teamwork, the sharing of knowledge and know-how, improved care, respect between professionals and better definition of solutions to cases. Through the analysis of the studies, 80 recommendations for improvement of communication were evidenced, mainly focused on aspects such as meetings, training, the use of Information and Communication Technologies, individual and inter-individual professional attitudes, spaces for formal and informal communication, organizational aspects, democratic and participatory management, and the role of leaders. In view of these findings, the present study reinforces Interprofessional Communication as an essential competence to the work process in Primary Health Care, which promotes collaborative and effective team care. In addition, the synthesized evidence can contribute to the development of managerial and educational interventions to strengthen the culture of communication and interprofessional collaboration among professionals working in Primary Care.